Peran Pelatihan Shalat Khusyuk dalam Menurunkan Kecemasan Pasien Gagal Ginjal Kronik yang Menjalani Hemodialisis - Kiki Ramiza; Fuad Nashori; Rr. Indahria Sulistyarini (Personifikasi: Jurnal Ilmu Psikologi, 2023)
The purpose of this study was to observe the effect of solemn pray training against the level of anxiety of chronic renal failure patients that are undergoing hemodialysis. The number of participants was eight chronic renal failure patients that are undergoing hemodialysis for less than 1 year to 1,5 years. The participants were divided into two groups, which were experiment and control groups in which each group consist of four members. This study was conducted using the experimental design with the measurements prior to and after the training, and also the follow-up that was done two weeks after the training. The training has lasted three sessions (380 minutes). The level of anxiety was measured using the scale of DASS (Depression, Anxiety, and Stress Scale). The training module referred to the theory of “Menggapai Shalat Khusyuk” by Al-Ghazali. Results of the study indicated that there was a significant effect of solemn pray training against the level of anxiety after the training. This study showed that the training can be used as of the therapies for decreasing the anxiety level of chronic renal failure patients undergoing hemodialysis.